Safety and Efficacy of Cabozantinib for Metastatic Nonclear Renal Cell Carcinoma: Real-world Data From an Italian Managed Access Program. (January 2019) - Prisciandaro, Michele; Ratta, Raffaele; Massari, Francesco; Fornarini, Giuseppe; Caponnetto, Salvatore; Iacovelli, Roberto; De Giorgi, Ugo; Facchini, Gaetano; Scagliarini, Sarah; Sabbatini, Roberto; Caserta, Claudia; Peverelli, Giorgia; et al.
Abstract : Objective: The activity of cabozantinib in nonclear cell histologies has not been evaluated. Materials and Methods: Data were collected across 24 Italian hospitals. Patients were aged 18 years and older with advanced nonclear cell renal cell carcinoma (RCC), with an Eastern Cooperative Oncology Group Performance Status 0 to 2, who had relapsed after previous systemic treatments for metastatic disease. Cabozantinib was administered orally at 60 mg once a day in 28 days cycles. Dose reductions to 40 or 20 mg were made due to toxicity. Adverse events (AEs) were monitored using CTCAE version 4.0. Results: Seventeen patients were enrolled. Three (18%) patients were diagnosed type I papillary RCC, 9 (53%) type II papillary, 3 (18%) chromophobe, and 2 (11%) with Bellini duct carcinoma. In total, 11 patients started with 60 mg. Six patients started a lower dose of 40 mg. Median progression-free survival was 7.83 months (0.4 to 13.4 mo), while median overall survival was not reached but 1-year overall survival was about 60%. Six patients (35%) experienced a partial response to treatment and 6 patients (35%) showed a stable disease. In the remaining 5 (30%), we observed a progressive disease. Grade 3 and 4 AEs were observed in 41% of patients. Among 20 patients, only 1 (6%) discontinued treatment due to AEs. Asthenia (41%), diarrhea (35%), aminotransferase increasing (35%), mucosal inflammation (35%), hand and foot syndrome (24%), and hypothyroidism (24%) were the most frequently AEs. Conclusions: Our data showed that, cabozantinib is a active and feasible treatment in patient with nonclear cell RCC.